Kult Świętego Rocha jako czynnik integrujący rodzinę i społeczność lokalną (na przykładzie parafii Mikstat w Południowej Wielkopolsce) - Strzelec, Małgorzata (Ecclesia. Studia z Dziejów Wielkopolski, 2010)
The Mikstat Parish is situated in the south of the Province of Wielkopolska, Poland. On the Cemetery Hill there is a small wooden church dedicated to St Roch, who has been venerated there for almost three hundred years. The local community are aware of the unusual vitality and form of this cult. The Saint Roch feast is a truly exceptional event there. St Roch is the protector of domestic animals who keeps them safe from infectious diseases. The feast celebrations and the patron saint integrate families and the local community. Many people try to participate in the feast preparations. As animals are blessed on this occasion, parishioners and visitors from all over Poland bring their animals and pray to St Roch to protect them. The cult of St Roch in this community also integrates families, because the celebrations are attended by whole families, including relatives residing outside the parish. In 2007 St Roch was pronounced patron saint of the town of Mikstat.